Gender-based violence, religion and forced displacement: Protective and risk factors - Pertek, Sandra; Block, Karen; Goodson, Lisa; Hassan, Pakinam; Hourani, Jeanine; Phillimore, Jenny (Frontiers in Human Dynamics, 2023)
This paper examines the relationship between gender-based violence (GBV) and religion in a range of forced displacement contexts. While it is acknowledged that religion frequently shapes experiences of GBV survivors, little is known about the influences of religion on GBV experiences in forced displacement and how it may be used to strengthen interventions. Utilising empirical evidence from 58 interviews with forced migrants in Sweden, UK, Turkey and Australia, we outline the interactions between religious resources and GBV in migrants’ forced displacement experiences. We draw on religious resources as comprising religious ideas, religious practices, religious experience and religious organisations. Our analyses advance the understanding of religious resources as both protective and risk factors that affect forced migrants’ experiences of GBV over time and place. We suggest a way forward for practitioners and researchers to account for the role of religion in experiences of GBV and forced displacement and to work with religious leaders and local faith communities to strengthen protection of survivors.